Development and Validation of a Scoring System for Early Diagnosis of Malignant Pleural Effusion Based on a Nomogram - Wu, Aihua; Liang, Zhigang; Yuan, Songbo; Wang, Shanshan; Peng, Weidong; Mo, Yijun; Yang, Jing; Liu, Yanqing (Frontiers in Oncology, 2021)
Background: The diagnostic value of clinical and laboratory features to differentiate between malignant pleural effusion (MPE) and benign pleural effusion (BPE) has not yet been established. Objectives: The present study aimed to develop and validate the diagnostic accuracy of a scoring system based on a nomogram to identify MPE from BPE. Methods: A total of 1239 eligible patients with PE were recruited in this study and randomly divided into a training set and an internal validation set at a ratio of 7:3. Logistic regression analysis was performed in the training set, and a nomogram was developed using selected predictors. The diagnostic accuracy of an innovative scoring system based on the nomogram was established and validated in the training, internal validation, and external validation sets (n = 217), respectively. The discriminatory power, calibration and clinical values of the prediction model were evaluated. Results: Seven variables (effusion carcinoembryonic antigen (CEA), effusion adenosine deaminase (ADA), erythrocyte sedimentation rate (ESR), PE/serum CEA (CEA ratio), effusion carbohydrate antigen 19-9 (CA19-9), effusion cytokeratin 19 fragment (CYFRA 21-1), and serum lactate dehydrogenase (LDH) to effusion ADA (cancer ratio, CR)) were validated and used to develop a nomogram. The prediction model showed both good discrimination and calibration capabilities for all sets. A scoring system was established based on the nomogram scores to distinguish MPE from BPE. The scoring system showed a favorable diagnostic performance in the training set (areas under the curve (AUC), 0.955; 95% confidence interval (CI), 0.942-0.968)), the internal validation set (AUC, 0.952; 95% CI, 0.932-0.973)), and the external validation set (AUC, 0.973; 95% CI, 0.956-0.990)). In addition, the scoring system achieved satisfactory discriminative abilities of separating lung cancer-associated MPE from tuberculous pleurisy effusion (TPE) in the combined training and validation sets. Conclusions: The present study developed and validated a scoring system based on seven parameters. The scoring system exhibited a reliable diagnostic performance in distinguishing MPE from BPE and might guide the clinical decision-making.